2011
DOI: 10.1007/s11274-011-0858-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wetland degradation on bacterial community in the Zoige Wetland of Qinghai-Tibetan Plateau (China)

Abstract: Wetland degradation makes significant impacts on soil, and bacterial communities in soil are likely to respond to these impacts. The purpose of this study was to investigate the impacts of soil property, soil type and soil depth on bacterial community in different stages of soil degradation in the Zoige Wetland. Microbial biomass carbon was estimated from chloroform fumigation-extraction. Bacterial communities were evaluated by cluster and principal component analysis of DGGE banding patterns and sequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…The average porewater pH of the HY and DX peatland was 6.3 and in MD it was 7.8, which could explain the relatively low Acidobacteria abundances observed. In agreement with our results, a previous study also did not detect Acidobacteria by DGGE in peatland of Zoige plateau close to where HY wetland is located [14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The average porewater pH of the HY and DX peatland was 6.3 and in MD it was 7.8, which could explain the relatively low Acidobacteria abundances observed. In agreement with our results, a previous study also did not detect Acidobacteria by DGGE in peatland of Zoige plateau close to where HY wetland is located [14].…”
Section: Discussionsupporting
confidence: 93%
“…The microbiological research in this region has been primarily restricted to specific functional groups of microorganisms, such as methanogens [8], [9] and methanotrophs [10], [11], or microbes involved in other specialized processes [12], [13]. In addition, a few cultivation-independent studies using denaturing gradient gel electrophoresis (DGGE) fingerprinting and limited clone library construction have been carried-out to assess the bacterial diversity in wetlands of this region [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of peatlands in northern Manitoba, Canada, Ise et al (2008) found that a falling water table increased the sensitivity of peat decomposition to temperature. Soil water content in the alpine wetlands was high, which depressed air diffusion, enzyme activity, and substrate availability (Rey et al 2005;Tang et al 2012;Wang et al 2010); this may have obscured the influences of increasing temperature and resulted in a lack of significant differences in Q 10 among different alpine wetlands. Moreover, the alpine wetlands were rich in high-quality SOM, therefore Q 10 values should not increase significantly until betterquality SOM is progressively depleted (Hartley and Ineson 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Huahu Lake is the highest alpine lake in Zoige and has typical watertable gradients from alpine wetland to alpine meadow (Chen et al 2011). A decline in wetland area and water table has been observed in past decades in this region (Tan et al 2012;Tang et al 2012;Zhang et al 2011). …”
Section: Study Areamentioning
confidence: 96%
“…The drier marsh meadow and dry meadow lands had a better soil environment to promote higher plant diversity, with a more complex litter composition that decomposed faster, correlating with a fungal composition dominated by Ascomycota and Basidiomycota. Tang (2012) found that soil microbial community compositions change according to water logging time, plant diversity and altitude. Zhao (2011) inferred that soil microbial community compositions were different in different plant diversity wetlands.…”
Section: Discussionmentioning
confidence: 99%